Resolving Intergenerational Conflict over the Environment under the Pareto Criterion - Torben M. Andersen; Joydeep Bhattacharya; Pan Liu (Center for Economic Studies and ifo Institute (CESifo), 2016)
We describe a “business as usual” (BAU) economy in which pollution is a by-product of productive activity by the current generation but “damages” production for future generations. Over time, conditions in the BAU economy become dire: it gets increasingly polluted, consumption falls and generational welfare levels decline. A government introduces costly pollution abatement and finances it via distorting taxes and borrowing on perfect international markets. Pollution levels start to decline, generating downstream welfare gains, some of which the government taxes away, without hurting anyone, to help pay off the debt, that too, in finite time. Along the transition, every generation faces less pollution, consumes more and is happier than if life had continued in the BAU world.
Keywords: O44; Q56; H50; 330; pollution; abatement; debt; environmental policy; Pareto criterion